Challenges Of Corporate Social Responsibility In The Niger Delta Region Of Nigeria - Ijaiya, Hakeem (Journal of Sustainable Development Law and Policy, 2025)
The Niger Delta Region of Nigeria produces a significant portion of the aggregate oil wealth of Nigeria. Since 1956 when oil was first struck in Oloibiri in Southern Nigeria, the Niger Delta region has accounted for over 90 per cent of Nigeria’s oil income. However, the region has perennially suffered from environmental neglect, crumbling infrastructures and services, high unemployment, social deprivation, abject poverty and endemic conflict. This has led to calls for oil companies operating in the Niger Delta to demonstrate the value of their investments to Nigeria by undertaking increased community development initiatives that provide direct social benefits such as local employment, new infrastructure, schools, and improved health care delivery. This paper examines the concept of Corporate Social Responsibility (CSR) that is, how companies manage their oil exploration and business processes to produce an overall positive impact on society. It reviews the evolution and growth of the CSR concept under international law and the key institutions that have spearheaded this growth. Since the emergence of the CSR concept in Nigeria, it has been espoused mainly as an optional and non-obligatory responsibility for oil companies. There is currently no national law in the area of CSR. More so, many of the International Corporate Responsibility Instruments, such as, the Organization for Economic Cooperation and Development (OECD) Guidelines for Multinational Enterprises; United Nations (UN) Global Compact and the 1998 ILO Declaration on Fundamental Principles and Rights at Work are soft law instruments with less binding status in international law and by extension in Nigeria. This paper examines the need for a more coherent and binding recognition of the CSR principle in Nigeria. In a country such as Nigeria, where the principles and benefits of democratic governance are still fragile, there is a need for a dynamic and step-wise approach through which the CSR concept could be continually mainstreamed into national laws and policies.